Sustainable Utilization of Industrial Solid Waste in Lightweight Concrete Blocks to Support Environmentally Friendly Cities - Lisa Oksri Nelfia; Mindy Barend Wiguno; Krisma Adijaya Adijaya; Yohans Sunarno; Ouali Amiri (Universitas Trisakti, 2026)
Aim: This study aims to evaluate the influence of gold tailings waste (GTW), nickel slag (NS), and rejected plastic (RP) as partial substitutes for cement and fine aggregates on the mechanical and physical properties of lightweight concrete blocks for sustainable construction applications. Methodology and Results: GTW was substituted at 5% by weight of cement, while NS and RP replaced fine aggregates at variations of 10–20% and 10–15%, respectively. Concrete specimens were cast, cured, and tested in accordance with SNI and ASTM standards. Compressive strength and density were measured at 7, 14, and 28 days, while splitting tensile strength and porosity were evaluated at 28 days. The results show that compressive strength increased with curing age, reaching 1.56–2.37 MPa at 28 days. The optimal mixture (BR 5GTW 20NS 10RP) achieved 1.93 MPa, exceeding the minimum SNI requirement of 1.8 MPa for lightweight concrete blocks. Density values ranged from 683 to 1001 kg/m³, confirming the lightweight classification. Splitting tensile strength ranged between 0.315 and 0.388 MPa, while porosity varied from 4.38% to 8.12%, indicating acceptable physical performance. Conclusion, Significance, and Impact of the Study: The incorporation of GTW, NS, and RP enhances mechanical performance while maintaining appropriate density and porosity. This approach offers a sustainable and cost-effective construction material by valorizing industrial waste, reducing environmental burdens, and supporting environmentally responsible urban infrastructure development.